Pengaruh Lingkungan Sekolah, Minat Belajar, Dan Sosial Ekonomi Keluarga Terhadap Hasil Belajar Siswa SMKS Tamansiswa Jetis Yogyakarta: Inggris, Indonesia - Satrio Sektining Bimo; Ibnu Siswanto (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2025)
Abstract This research aims to determine whether the school environment, interest in learning, and family socio-economics influence partially or simultaneously the learning outcomes of students majoring in Motorcycle Engineering at SMKS Tamansiswa Jetis Yogyakarta for the 2023/2024 academic year. Quantitative research methods are used with an ex-post facto type of research. This study's population was 100 students, and the data collection techniques used were questionnaires and documentation. The data analysis technique in this research uses 1) descriptive analysis, 2) simple regression analysis, and 3) multiple regression analysis. The research results show that: 1) The school environment influences learning outcomes with a relationship or correlation of 0.283; 2) Students' learning interest has an influence on learning outcomes with a relationship or correlation of 0.320; 3) Family socio-economics has an influence on learning outcomes with a relationship or correlation of 0.438; 4) The school environment, interest in learning, and family socio-economics simultaneously have an influence on student learning outcomes in the Motorcycle Engineering Department of SMKS Tamansiswa Jetis Yogyakarta, having a relationship or correlation of 0.444, and the contribution is 19.7%. Keywords: School Environment; Interest in Learning; Family Socio-Economics; Learning Outcomes Abstrak Penelitian ini bertujuan untuk mengetahui lingkungan sekolah, minat belajar, dan sosial ekonomi keluarga mempengaruhi secara parsial maupun simultan terhadap hasil belajar siswa Jurusan Teknik Sepeda Motor di SMKS Tamansiswa Jetis Yogyakarta tahun pelajaran 2023/2024. Metode penelitian kuantitatif digunakan dalam penelitian ini dengan jenis penelitian ex-post facto. Pada penelitian ini populasi berjumlah 100 siswa dan teknik pengumpulan data yaitu kuesioner dan dokumentasi. Teknik analisis data pada penelitian ini menggunakan 1) analisis deskriptif, 2) analisis regresi sederhana, dan 3) analisis regresi berganda. Hasil penelitian menunjukkan bahwa: 1) Lingkungan sekolah memiliki pengaruh terhadap hasil belajar dengan hubungan atau korelasinya sebesar 0,283; 2) Minat belajar siswa memiliki pengaruh terhadap hasil belajar dengan hubungan atau korelasinya sebesar 0,320; 3) Sosial ekonomi keluarga memiliki pengaruh terhadap hasil belajar dengan hubungan atau korelasinya sebesar 0,438; 4) Lingkungan sekolah, minat belajar, dan sosial ekonomi keluarga secara simultan memiliki pengaruh terhadap hasil belajar siswa Jurusan Teknik Sepeda Motor SMKS Tamansiswa Jetis Yogyakarta mempunyai hubungan atau korelasi sebesar 0,444, dan kontribusinya sebesar 19,7%. Kata kunci: Lingkungan Sekolah; Minat Belajar; Sosial Ekonomi Keluarga; Hasil Belajar